2018
DOI: 10.7897/2230-8407.09684
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Microwave-Assisted Extraction (Mae) of Medicinal Plants: A Review

Abstract: Since the last decade, there is enhanced interest for the use of Microwaves for the extraction (MAE) of the constituents of plant material. This review gives a brief theoretical background on MAE the principles and the types of instruments used have been presented. The main parameters like microwave power, extraction time, solvents, temperature and effect of stirring, etc., which influence the MAE have been discussed. Through numerous examples, it is demonstrated that this technique allows reduced solvent cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…In the present study, microwave extraction method was applied using less solvent and less time spent with effective higher yield. Earlier many research articles are the evidences for positive application of microwave extraction for plant material extraction (Saleh et al, 2017;Alara et al, 2018;Al-Mamoori and Al-Janabi, 2018). Based on that concept, in this investigation, microwave extraction gave higher yield in less time and with less solvent application.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, microwave extraction method was applied using less solvent and less time spent with effective higher yield. Earlier many research articles are the evidences for positive application of microwave extraction for plant material extraction (Saleh et al, 2017;Alara et al, 2018;Al-Mamoori and Al-Janabi, 2018). Based on that concept, in this investigation, microwave extraction gave higher yield in less time and with less solvent application.…”
Section: Discussionmentioning
confidence: 75%
“…Studies have shown that stirring can help in achieving better extraction efficiency by facilitating the penetration of the solvent into the plant material, thereby enhancing the extraction of bioactive compounds. Proper stirring can also prevent localized heating and ensure consistent extraction throughout the sample, contributing to the overall effectiveness of the MAE process [68].…”
Section: Microwave-assisted Extraction (Mae)mentioning
confidence: 99%
“…Several strategies are used toward the isolation and purification of coumarin compounds. Maceration, reflux, ultrasonic-assisted, and microwave extraction are current methods for the preparation of the crude extract containing IF [ 29 , 78 , 79 , 80 ]. These methods of extractions were conducted in the presence of various solvents including medium polar or non-polar solvents such as ethyl acetate (EtOAc) [ 69 ], diethyl ether [ 44 ], and hot polar ones such as hot ethanol (EtOH) [ 81 ], hot methanol (MeOH) [ 39 ], and hot deionized water (W) [ 82 ].…”
Section: Isofraxidinmentioning
confidence: 99%